The impact of service quality on customer satisfaction, a study on Tanjung Offshore Services / Alia Zafira Saleh - Saleh, Alia Zafira (Faculty of Business and Management, 2007)
As market growth slows or as markets become more competitive and level of switching costs increase, firms are more likely to attempt to maintain their market share by focusing on retaining current customers. Service Quality has been advocated as an easier and more reliable source of customer satisfaction. This research utilized a convenience methodology to improve customer satisfaction, and the researcher has helped the firm identifying the factors that contribute to retain customer and initiate a variety of strategies to accomplish this objective. Five dimensions that contribute to retain customer that had been identify by researcher consists of tangible, responsiveness, reliability, assurance and empathy. The findings highlight that all the five dimensions do contribute to customer satisfaction and the firm should take action and focus more on these five contribution factors or dimensions in order to retain and keep their customers loyal. The researcher also identified the causes that lead to the decrease of the firm customer retention rate and had come out with few recommendations. The recommendations that can be taken into consideration such as formation of customer-contact-employee relationship, effective communications to build trust and establish customer loyalty programme. By implementing these three recommendations, the researcher optimism that it will help the firm to better upgrade its performance and any area that is not running well in their management for future use.